Pengaruh Model Pembelajaran Two Stay Two Stray (TSTS) Terhadap Keterampilan Menyimak Siswa Kelas V Sekolah Dasar - Annisa Ulhasanah; Eddy Noviana; Intan Kartika Sari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This study aims to determine the effect of using the Two Stay Two Stray (TSTS) learning model on the listening skills of fifth-grade students. The research was conducted in classes VB and VC at UPT SDN 015 Sumber Sari, involving a total of 62 students, during the odd semester of the 2024/2025 academic year, specifically in July 2024. The study utilized a Non-Equivalent Control Group Design, involving two classes: VC as the experimental class with 32 students and VB as the control class with 30 students. In the experimental class, learning was conducted using the Two Stay Two Stray (TSTS) model, while in the control class, conventional teaching methods were applied. Students' listening skills were assessed through pretests and posttests in audio format, each consisting of 20 questions. The data collected were analyzed using normality tests, homogeneity tests, and hypothesis testing through the SPSS 24 application. The results showed that hypothesis testing using the t-test produced a significance value of 0.000 < 0.05, indicating that Ha was accepted and Ho was rejected. These findings suggest a significant effect of applying the Two Stay Two Stray (TSTS) learning model on students' listening skills. This improvement was evident from the average posttest scores, with the experimental class achieving an average of 83.48, higher than the control class's average of 71.74. Thus, this study confirms that the use of the Two Stay Two Stray (TSTS) model is effective in enhancing the listening skills of fifth-grade elementary school students.